The determinants of government bond yields in Malaysia / Nur Nadiatulhusna Mohammad Zohir - Mohammad Zohir, Nur Nadiatulhusna (2019)
This paper examines the relationship between government bond yields and macroeconomic determinants such as Federal Government Budget Deficit, Government Debt, Consumer Price Index (CPI) and Short- term Interest Rate. Secondary data was collected from Bloomberg, Bank Negara Malaysia and World Bank from year 2013-2014 which contain quarterly data and have a total of 24 observations in this paper. Ordinary Least Square (OLS) method was employed to run the model and estimate the regression. Besides, this paper also employed the Breusch- Godfrey Serial Correlation LM test, Autocorrelation, Multicollinearity and Hetroscedasticity (ARCH) test, Jarque- Bera test and encounter that there is no serious multicollinearity problem, no autocorrelation, no heteroscedasticity, and error term is normally distributed and model is correctly specified. These empirical results help investors to determine the factors that could affect the government bond yields and to make easier decision making.